Strawson's concept of a person and its implications for psychology - Richter, Alan Leon (Department of Psychology, 2023)
ln this work I Shall introduce Strawson concept of a person and elucidate its ontological and epistemological aspects, I shall then examine criticism of Strawson's work, and deal with Strawson general approach, the origins and development of his work and., finally the implications of his concept of a person psychology.